Analysis of the physical performance of national team athletic athletes in preparation for international competitions: A multidimensional approach - Wiriawan, Oce; Lolita, Yuri; Setijono, Hari; Turi, Moh (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of anthropometry, premeter tests, and general physical condition on the performance of athletic athletes at the national training center in Jakarta. Using a quantitative survey approach, Structural Equation Modeling (SEM) with the PLS method was employed to analyze relationships between variables. The study involved 15 athletes, consisting of 7 track athletes and 8 field athletes. Data were processed using SPSS 25 and Smart PLS-SEM.The results indicate that anthropometry has a small positive effect on athletic performance, with an original sample value of 0.15, a t-statistic of 1.96, and a P-value of 0.66 (>0.05). The premeter test significantly influences performance, with a positive original sample value of 0.44, a t-statistic of 3.40 (>1.96), and a P-value of 0.000 (<0.05). General physical condition quality significantly affects achievement, with an original sample value of 0.49, a t-statistic of 2.15 (>1.96), and a P-value of 0.007 (<0.05). These findings highlight the importance of general physical condition and premeter testing in enhancing athlete performance, while anthropometry has a limited impact. This study provides valuable insights into the factors influencing performance in athletics.